Study of early neonatal outcomes in babies delivered through meconium-stained amniotic fluid in a rural teaching hospital - Dhannaram, Venkatesh; Kotapuri, Sumathi; Chitgupikar, Sudharshanraj (International Journal of Contemporary Pediatrics, 2021)
Background: When the fetus is in a state of stress meconium is passed presence of meconium in amniotic fluid is potentially a serious Sign of fatal compromise, frequency of meconium strained amniotic fluid ranges from 5-22%. MSAF results in higher rate of cesarean delivery, NICU admission rate, respiratory distress, PPHN and neonatal death. The primary objectives of the study were to estimate the incidence of Meconium aspiration syndrome & Respiratory distress among babies born through meconium-stained amniotic fluid (MSAF) along with studying the outcomes at the end of 7 days. Methods: This was a prospective study undertaken in mediciti institute of medical sciences, Ghanpur Medchal Mandal from Jan 2018 to June 2019. Data was collected in a predetermined proforma after institutional ethical committee clearance and appropriate informed consent. Results: During this period 1972 neonates were delivered of which 216 babies were born through MSAF. 18 were excluded for non-cephalic presentation, multiple gestation or congenital anomalies.198 babies were included in the study (96 male and 102 female). 18 neonates (10.2%) needed resuscitation at birth. 85 (42.9%) had thick MSAF. 43 of them developed respiratory distress (21.7%). 10 babies were ventilated. Seizures, hyperbilirubinemia, thrombocytopenia were more common among babies with thick MSAF. Mortality was 1%. Conclusions: Thick meconium-stained amniotic fluid was associated with low Apgar score, higher rate of emergency cesarean section and meconium aspiration syndrome. Primigravida mothers, maternal hypothyroidism and oligohydramnios were important risk factors associated with MAS.